2002
DOI: 10.1182/blood.v99.9.3228
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein VI–mediated platelet fibrinogen receptor activation occurs through calcium-sensitive and PKC-sensitive pathways without a requirement for secreted ADP

Abstract: Collagen activates platelets by transducing signals through glycoprotein VI (GPVI). It is not clear whether collagen can directly activate fibrinogen receptors on the adherent platelets without a role for positive feedback agonists. We investigated the contribution of secondary G protein signaling to the mechanism of GPVI-stimulated platelet aggregation using the GPVI-selective agonists, convulxin and collagen-related peptide (CRP) as well as collagen. Adenosine diphosphate (ADP) scavengers or ADP receptor ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 48 publications
2
50
0
Order By: Relevance
“…However, these agents are not physiological agonists, and the physiological relevance of these pathways is not clear. Recent studies demonstrated that these pathways are important for glycoprotein VImediated platelet fibrinogen receptor activation [38,39]. Using a combination of agonists, antagonists and inhibitors with established effectiveness [6,7,10,34,40], this paper demonstrates Signalling pathways in fibrinogen receptor activation that platelets contain a calcium-regulated pathway and a PKC-regulated pathway, downstream of PLC activation, that independently regulate agonist-induced fibrinogen receptor activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these agents are not physiological agonists, and the physiological relevance of these pathways is not clear. Recent studies demonstrated that these pathways are important for glycoprotein VImediated platelet fibrinogen receptor activation [38,39]. Using a combination of agonists, antagonists and inhibitors with established effectiveness [6,7,10,34,40], this paper demonstrates Signalling pathways in fibrinogen receptor activation that platelets contain a calcium-regulated pathway and a PKC-regulated pathway, downstream of PLC activation, that independently regulate agonist-induced fibrinogen receptor activation.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of SFLLRN and U46619, fibrinogen receptor activation was abolished when both PKC-and calcium-regulated pathways were blocked, even when supplemented with G i signalling (Figures 5 and 6). This system has recently been proposed in non-GPCR-mediated platelet activation where PKC activation and increased calcium are required for full aggregation induced by the glycoprotein VI agonist convulxin [38,39]. ADP appears to utilize only the calcium-regulated pathway ; this is not unexpected, since ADP minimally activates PKC and its activity is much less compared with that for U46619 and SFLLRN, as shown by pleckstrin phosphorylation.…”
Section: Figure 6 Effect Of G I Signalling On Sfllrn-induced Plateletmentioning
confidence: 99%
“…Collagen-induced platelet dense granule secretion and aggregation markedly rely on intermediate TXA2 signalling, whereas this dependency accounts for convulxin-provoked platelet activation at low but not high agonist-concentrations [25,26].…”
Section: Platelet Dense Granule Secretion and Aggregation In Responsementioning
confidence: 99%
“…Importantly, the GIRK channel inhibitors did not affect platelet aggregation induced by high concentrations of thrombin (1 U/mL; Figure 2E), AYPGKF (not shown), or convulxin (100 ng/mL), a glycoprotein VI agonist (data not shown), which is known to occur independently of P2Y 12 receptor activation. 5,57 To investigate the specificity of SCH23390 toward blocking GIRK channels we used SKF38393, which is structurally related to SCH23390 but inactive at blocking GIRK channels. 45 We evaluated the effect of SKF38393 (200 M) on ADP-, 2-MeSADP-, U46619-, and low-dose thrombin-induced aggregation.…”
Section: Effect Of Girk Inhibitors On Agonist-induced Platelet Aggregmentioning
confidence: 99%